Archives of Autogestion - Timothy Gibbs (Revue Internationale des Études du Développement)
One strategy to decentre and create a more polycentric model of the history of international development is to focus on influential alternative models of development practice formulated at specific moments in particular places in the Global South. Hence this article about the attempt of an influential cluster of new-left, anti-apartheid activists to create a new sort of democratic, grassroots-focused, urban planning expertise and archives in South Africa that promoted self-help housing (autogestion). By tracing the professional biographies and institutional trajectories of this generation of South African new-left activists we might analyse their attempts to implement a counter-hegemonic, grassroots, participatory developmental project.